Research Progress of Neonatal Jaundice 2013-2023: a Bibliometric Analysis - Martanti, Listyaning Eko; Amelia, Rizky; Rofi'ah, Siti; Ariyanti, Ida (Midwifery and Nursing Research, 2024)
Background: Jaundice or neonatal jaundice is a problem that occurs in neonates, especially in the first week of life, which is caused by the accumulation of bilirubin that exceeds the threshold in the blood and tissues. Dangerous complications such as encephalopathy and kernicterus can occur which can be fatal and cause mental retardation and neurological disorders in babies.Methods: We extracted all relevant publications about neonatal jaundice between 2013 and 2023 through the Scopus database with a total of 7336 articles with document type only article and review, keywords limited to newborn, infant, newborn jaundice and English language. VOSviewer software was used to visualize trends in neonatal jaundice research from the perspective of co-occurring keywords.Results: There are fluctuations in article growth from year to year, but there has been a significant increase in 2021 of around 18.93%. The United States contributed the largest number of publications with 571 articles followed by China and India. Canada ranks first with the highest citations, the Journal of Maternal Fetal and Neonatal Medicine is the journal that publishes the most articles about neonatal jaundice with a citation ranking of 87. Key words that often appear are bilirubin, deficiency, disease.Conclusion: It is still a big and important opportunity to research the breastfeeding variable with a public health approach because it still rarely appears in findings for the keyword neonatal jaundice